Ultrasound Stimulate Conjugation Between Wild Type and Genetically Engineered Agrobacterium tumefaciens and Sinorhizobiummeliloti - Raghad Nawaf Gergees Al-Zaidy (Journal of Global Pharma Technology, 2019)
Bacterial conjugations represent one of possibilities that transform bacteria. This study aimed to detect the occurrence of conjugation between two genera of bacteria includes wild strain A.tumefaciens (Atmco1), standard strain A. tumefaciens (C58Cl) and Sinorhizobiummeliloti. The results proved the conjugation through the sensitivity of those bacteria to specific antibiotics. The obtained data reported the stimulation of bacteria growth when they exposed to different ultrasound treatments. These ultrasound treatments include five period (0.0, 240, 480, 720 and 900) second for (47.6) KHZ. The treatments (240, 480) s increase colonies numbers between 25-72% when bacteria grown on the surface of the specific solid medium. The interesting results of this study are that the exposures of the conjugation mixture to the ultrasound treatment increase the Trans conjugant colonies between (23-80) % and increase the conjugation frequency twice. This may be probably as akey to enhance conjugation between those of bacteria species which are not able to conjugation.